Ask the Experts: The future of neurodegenerative diseases: emerging targets, treatments and technologies. (September 2012) - Voss, John; Ebert, Allison; Wolfe, Michael; Lindsley, Craig; Cookson, Mark; Deane, Rashid
The field of medicinal chemistry applied to the discovery of novel and efficacious therapy for neurodegenerative diseases is ever changing as new molecular targets, compounds and technologies are discovered. Isaac Bruce, Commissioning Editor, spoke to six experts and discussed why they became involved in the field, the future of the area and the challenges it faces.